Effects of BOSU® ball balance training on balance ability and proprioception in adults with ankle instability - Choi, Jung-Hyun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Lower limb muscle strength training and balance training are effective in improving and preventing ankle instability. In the present study, we aimed to investigate the effects of balance training with a BOSU® Ball on balance ability and proprioception in adults with ankle instability. Methods/Statistical analysis: Twenty-six adults in their twenties with ankle instability were selected and randomly assigned to either the BOSU® Ball exercise group (BBG; n=13) or the Thera-band exercise group (TBG; n=13). The intervention was carried out three times a week for four weeks, for a total of twelve times. Proprioception and balance ability tests were performed before and after the intervention. Findings: Proprioception significantly decreased for the BBG (p